2016 IEEE Compound Semiconductor Integrated Circuit Symposium (CSICS) 2016
DOI: 10.1109/csics.2016.7751062
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable RF Components for Multifunction RF Systems

Abstract: The proliferation of the wireless market has driven the demand for RF systems to dramatically increase functionality, frequency coverage, bandwidth, and efficiency; while simultaneously reducing power consumption and die size to save power and cost. For example, the highly complex RF systems in handset technology have seen a dramatic increase in frequency, operating bands, and complexity of signals with each generation (from 1G to 4G). The next generation (5G) will continue the trend to extend the frequency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Introducing additional zeros close to the passband while maintaining the flexibility of their placement is highly desired and can be achieved using our proposed topology, as will be demonstrated. Although others have proposed filters with multiple zeros in the transmission response, to the best of our knowledge, no previous researchers have demonstrated the ability to control their placement on either side of the passband. Indeed, in Goron et al, three transmission zeros were achieved using an asymmetric feed point topology with two of the zeros fixed in the upper side band of the filter.…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing additional zeros close to the passband while maintaining the flexibility of their placement is highly desired and can be achieved using our proposed topology, as will be demonstrated. Although others have proposed filters with multiple zeros in the transmission response, to the best of our knowledge, no previous researchers have demonstrated the ability to control their placement on either side of the passband. Indeed, in Goron et al, three transmission zeros were achieved using an asymmetric feed point topology with two of the zeros fixed in the upper side band of the filter.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Because this process offers a high dielectric constant that produces physically small filters at the expense of higher dielectric loss compared to the Duroid substrate, there was little need for further size reduction. Figure depicts a 3D representation of the model used for EM simulation, where the filters can be readily identified, and shows a picture of the circuit fabricated at the LTCC@ETS facilities . The measurement results for both the Duroid and LTCC circuits are discussed in section 4.…”
Section: Design and Simulationmentioning
confidence: 99%
“…However, due to the push for developing small satellites with enhanced system capabilities/ performance at lower cost, it is advantageous to develop a single wideband, reconfigurable high-power, high-efficiency SSMPM that can operate at multiple frequency bands depending on the need at any given time. Innovations in compound semiconductor materials, devices, and circuits to increase the functionality and reconfigureability of RF systems are reported in [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, a lot of research has reported multiband=multimode and reconfigurable RF systems such as tunable antennas, filters, power amplifiers, and matching networks. [1][2][3][4][5][6][7][8] In these systems, tunable capacitors are a key component. RF-MEMS tunable capacitors are more suitable for these systems than any other devices such as p-i-n diodes, silicon-on-insulator (SOI) switches, [9][10][11] or barium-strontium-titanate (BST) type tunable capacitors, 12) thanks to their low loss and excellent linearity.…”
Section: Introductionmentioning
confidence: 99%